Effect of handling material on mechanical and optical properties of feldspathic porcelain - Bitencourt, Sandro Basso [UNESP]; Bastos, Natália Almeida; Mazza, Letícia Cerri [UNESP]; Rangel, Elidiane Cipriano [UNESP]; De Souza, Grace Mendonça; da Silva Pereira, Flávia [UNESP]; Goiato, Marcelo Coelho [UNESP]; dos Santos, Daniela Micheline [UNESP]; Pesqueira, Aldiéris Alves [UNESP] (Wiley, 2020)
Objective: To evaluate the optical, chemical, and mechanical properties of feldspathic porcelain after handling with different instrument materials. Material and methods: Feldspathic porcelain was manipulated with different spatula compositions: metal spatula (MS), plastic spatula (PS), and glass spatula (GS) for the fabrication of 30 (n = 10) disks. Contrast ratio (CR), translucency parameter (TP), and surface Knoop microhardness (KHN) were measured. The color change (ΔE00) was evaluated using the CIEDE2000 system. Scanning electron microscopy (SEM) and energy-dispersive spectroscopy (EDS) were used for surface analysis. Data were analyzed using one-way ANOVA and Tukey test (P < 0.05). Results: All groups presented different morphological surfaces with higher presence of Al on the MS. PS group presented lower Al, Si, K than MS, and GS. Higher CR was observed for PS (0.734; P < 0.043), followed by MS (0.696; P < 0.043) and GS (0.65; P < 0.011). The highest TP (13.06) and KHN (386.27) were presented by GS (P < 0.001). MS and PS presented similar KHN results. The higher ΔE00 were found for plastic/metal comparison. Also, the L* values for the MS group (67.49) were lower than the other groups. Conclusion: The use of metal spatula promoted higher color alteration during feldspathic porcelain manipulation than did the other materials. Handling with glass instrument promoted higher microhardness than other spatula materials. Clinical significance: The effect of the material used for ceramic handling on feldspathic porcelain properties is often ignored. This study shows that the handling spatula material must be carefully chosen to avoid inadvertent changes to the feldspathic porcelain restoration.
Keywords: ceramics; color science; dental materials